2024
DOI: 10.1037/sgd0000592
|View full text |Cite
|
Sign up to set email alerts
|

Mental health care use among adolescent sexual minority males before and during COVID-19.

Abstract: Adolescent (cisgender) sexual minority males (ASMM) face multiple mental health disparities. Yet surprisingly little is known about use of mental health care among ASMM. The current study examined mental health care use among ASMM, both lifetime use and during the COVID-19 pandemic. ASMM (N = 154, ages 14–17 years) enrolled in Spring 2020 for a pilot randomized controlled trial of an online sexual health intervention. Participants were assessed at baseline and 3-month follow-up. Participants reported lifetime … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…The authors learned that while approximately 40% of the youth reported having received treatment for mental health concerns throughout their lifetime, only 20% of the youth reported receiving treatment for mental health during the COVID-19 pandemic. Perry and Nelson's (2022) findings highlight the gap in mental health care amongst SMI resulting from the systemic barriers to adequate health care services available during the COVID-19 pandemic.…”
Section: Covid-19: a Much-needed Spotlight On Public Health Provisionmentioning
confidence: 93%
See 2 more Smart Citations
“…The authors learned that while approximately 40% of the youth reported having received treatment for mental health concerns throughout their lifetime, only 20% of the youth reported receiving treatment for mental health during the COVID-19 pandemic. Perry and Nelson's (2022) findings highlight the gap in mental health care amongst SMI resulting from the systemic barriers to adequate health care services available during the COVID-19 pandemic.…”
Section: Covid-19: a Much-needed Spotlight On Public Health Provisionmentioning
confidence: 93%
“…While mental health concerns impact all members of society, studies have shown that mental health issues tend to affect members of sexual and gender minority communities at a greater level (Bränström et al, 2022;Jenkins et al, 2022;Kerr et al, 2022;Pease et al, 2022;N. S. Perry & Nelson, 2022;Pharr et al, 2019;Tabler et al, 2019;Tuthill et al, 2017).…”
Section: Mental Health Needs and Stigmatized Populationsmentioning
confidence: 99%
See 1 more Smart Citation